Situation awareness to support decision-making among emergency care practitioners - Abd Hamid, Harris Shah (2009)

(untitled)
Motivation – To understand a new work role in emergency medical services, the relationship between situation awareness (SA) and decision-making among emergency care practitioners (ECPs) is examined. Research approach – A scoping study was completed and involved observations (36 hours of ride-outs and 4 hours of sit-ins) and semi-structured interviews with a group of ECPs and Triage Nurses at an ambulance control room. A subject matter expert was consulted to validate a communication map derived from the observations and interviews. Findings/Design – The results show that system’s factors could affect the creation of SA and decision-making. As a result, a framework for SA and decision-making among ECPs was developed. Originality/Value – This study extends the study of SA into emergency medical services domain. It also contributes in understanding a new practitioner role in the UK. Take away message – Factors related to the development of SA should be understood to support decisionmaking among ECPs and thereby improve the quality of care in emergency medicine.